Copper-Catalyzed Decarboxylative Cascade Cyclization for the Synthesis of 2-Arylquinolines - Chatterjee, Rana; Pothireddy, Mohanreddy; Dandela, Rambabu (Synlett, 2023)
An efficient copper-catalyzed intermolecular decarboxylative cascade cyclization has been developed that uses readily accessible starting materials and less-expensive reagents. A one-pot reaction of an aryl aldehyde, an aniline, and acrylic acid permits the direct synthesis of 2-substituted quinolines through the sequential formation of C–N and C–C bonds. Furthermore, the three-component, one-pot, domino strategy features promising chemo- and regioselectivity and also tolerates a wide variety of substrates with excellent functional-group tolerance, high yields, a radical reaction pathway, and aerobic reaction conditions.
Keywords: copper catalysis; oxidative coupling; cascade reaction; cyclization; decarboxylation; quinolines